Natural products in food, beverages and plants - Gallo, Blanca (2020)
The chemical analysis of food and beverages has a huge interest in food science in order to develop deep knowledge of natural products, which can lead to an improvement of nutritional quality and manufacturing methods, as well as the detection of geographical origins, bad practices, adulterations and frauds.Polyphenols are a relevant group of natural products which are widely found in the Plant Kingdom. Due to their antioxidant, antimicrobial and antiparasitic properties these compounds have attracted attention for their many benefits for human health (e.g. cardiovascular diseases, cancer...), and have also been associated with the development of biotic resistance in plants. In addition, they are a key element in explaining some food properties, such as flavour, bitterness, astringency, aroma and colour.